Green supply chain nuances in east malaysian construction industry - Bamgbade, J.A.; Hosany, Mohammad Mehdi; Ajibike, W. A.; Chai, C.S. (Taylor & Francis Ltd., 2023)
The antecedent influence of technology innovation, regulatory regimes and stakeholders’ pressure on green supply chain management have been investigated disparately, with mixed results. This study aimed to explore the potential and specific effects of these selection pressure among sampled construction organizations in Sarawak Malaysia using the Triple Embeddedness Framework as an underpinning theory. Using a self-report online survey instrument, we sampled 350 contractors in Sarawak, and 114 responses were received after repeated reminders. However, after removing seven incomplete responses, only 107 usable surveys were considered for data analysis, denoting a response rate of 30.6%. Data screening was then carried out using SPSS version 23, while SmartPLS version 3.2 was used to assess the measurement and structural models. The findings suggest that regulatory pressure and technology orientation positively relate to the contractors’ green supply chain management. There is also a significant mediation of technology orientation in customer, regulatory pressure and green supply chain management relationships. This study contributes to the construction project supply chain body of knowledge by channelling the Triple Embeddedness Framework toward green supply chain management by providing empirical grounds from the hypothesized relationships. Stakeholders’ unification is also suggested for sustainable upstream and downstream integration.